Polluted lake restoration to promote sustainability in the Yangtze River Basin, China. Issue 1 (24th November 2021) - Qin, Boqiang; Zhang, Yunlin; Deng, Jianming; Zhu, Guangwei; Liu, Jianguo; Hamilton, David P; Paerl, Hans W; Brookes, Justin D; Wu, Tingfeng; Peng, Kai; Yao, Yizhou; Ding, Kan; et al.
Abstract : China has made a concerted effort to successfully improve water quality of rivers, but lake water quality has not improved. Lakes require controls on both catchment external nutrient loads and in-lake internal loads, where nature-based solutions are coupled with engineered systems to achieve the United Nations Sustainable Development Goals (SDGs).